(untitled) (CIPEEX, 2025)
This research project aimed to evaluate tooth discoloration caused by filling pastes used in pediatric dentistry. Blocks of bovine lower incisor crowns were prepared. A 2 mm thick remnant of enamel and dentin was obtained. The blocks were randomly distributed into 2 groups, according to whether or not dentin hybridization was performed. After hybridization, the blocks were subdivided into 5 experimental groups, according to the type of endodontic cement: 1) Guedes Pinto Paste; 2) Zinc oxide and eugenol paste; 3) Calcium hydroxide paste, prepared with p.a. calcium hydroxide and propylene glycol; 4) Paste containing Chloramphenicol + tetracycline chloride + zinc oxide and eugenol; 5) Vitapex®. Color determination was performed with a digital spectrophotometer and measurements were obtained 7, 30, and 60 days after material placement. Data regarding discoloration were tabulated and tested for normality using the Shapiro-Wilk test. ANOVA and Tukey tests were employed. Filling paste and evaluation period showed a statistical difference in tooth color change (p< 0.05). A higher level of staining was observed with the use of Guedes Pinto Paste (p<0.05). Filling pastes induce staining in the tooth structure. Coronal hybridization was not sufficient to prevent tooth staining. The contact time between the filling material and the tooth structure influenced the level of staining.